The Perspective of Azorean Early Childhood and Elementary School Teachers on Computational Thinking - Moniz Gata, Graça; Santos, Ana Isabel; Cascalho, José Manuel (Technium Education and Humanities, 2026)
Computational Thinking is now an innovative and effective pedagogical approach for promoting meaningful learning in preschool and elementary education, preparing children for the challenges and opportunities of the 21st century. In Portugal, CT has been part of the mathematics curriculum in the primary education since 2021. In 2022, a CT project began to be implemented in schools in the Autonomous Region of the Azores (ARA). To date, no studies have revealed how teachers are working in this area. This study seeks to understand how early childhood and primary school teachers work in public schools in the ARA view CT, considering the work that teachers report doing in various curricular areas to promote CT skills in children, in particular factors such as the necessary resources, skills to be promoted and activities implemented. This exploratory study used a questionnaire with open and closed questions, distributed by e-mail and answered by 81 teachers, and the data obtained was analyzed quantitatively and qualitatively. The results show that CT is a concept that is well known to teachers, that the skills involved are promoted in many schools in the Region, and that the activities carried out are varied. However, the study also indicates challenges in CT implementation, including the lack of teacher training and resources. Although it is a developing area, CT still needs to be explored further to enrich teachers' practices and maximize the knowledge and potential that can be gained from integrating CT-related activities into the curriculum.